Molecular basis underpinning MR1 allomorph recognition by an MR1-restricted T cell receptor - Suckling, Richard J.; Pamukcu, Cevriye; Simmons, Robert Alan; Fonseca, Daniel; Grant, Emma; Harrison, Rory; Shaikh, Saher A.; Khanolkar, Rahul C.; Ghadbane, Hemza; Creese, Andrew; Hock, Miriam; Gligoris, Thomas G.; et al. (Frontiers in Immunology, 2025)
IntroductionThe MHC-class-I-related molecule MR1 presents small metabolites of microbial and self-origin to T cells bearing semi-invariant or variant T cell receptors. One such T cell receptor, MC.7.G5, was previously shown to confer broad MR1-restricted reactivity to tumor cells but not normal cells, sparking interest in the development of non-MHC-restricted immunotherapy approaches.Methods/ResultsHere we provide cellular, biophysical, and crystallographic evidence that the MC.7.G5 TCR does not have pan-cancer specificity but is restricted to a rare allomorph of MR1, bearing the R9H mutation.DiscussionOur results underscore the importance of in-depth characterization of MR1-reactive TCRs against targets expressing the full repertoire of MR1 allomorphs.